2022
DOI: 10.3390/ijms23031639
|View full text |Cite
|
Sign up to set email alerts
|

Bone Health in Patients with Dyslipidemias: An Underestimated Aspect

Abstract: Beyond being aging-related diseases, atherosclerosis and osteoporosis share common pathogenetic pathways implicated in bone and vascular mineralization. However, the contributory role of dyslipidemia in this interplay is less documented. The purpose of this narrative review is to provide epidemiological evidence regarding the prevalence of bone disease (osteoporosis, fracture risk) in patients with dyslipidemias and to discuss potential common pathophysiological mechanisms linking osteoporosis and atherosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 140 publications
(146 reference statements)
0
37
0
Order By: Relevance
“…It has been observed that dyslipidemia elevates the concentrations of total and low-density lipoprotein (LDL) concentrations that are further associated with low bone mass and enhanced fracture risk. Dyslipidemia, enhances the activity of the osteoclasts by inducing oxidative stress and systemic inflammation, thereby reducing the formation of bone [ 79 ].…”
Section: Metabolism and Bone Related Diseasesmentioning
confidence: 99%
“…It has been observed that dyslipidemia elevates the concentrations of total and low-density lipoprotein (LDL) concentrations that are further associated with low bone mass and enhanced fracture risk. Dyslipidemia, enhances the activity of the osteoclasts by inducing oxidative stress and systemic inflammation, thereby reducing the formation of bone [ 79 ].…”
Section: Metabolism and Bone Related Diseasesmentioning
confidence: 99%
“…Recently, accumulated studies suggested that high cholesterol inhibits osteoblast differentiation and enhances osteoclastogenesis, thereby decreasing BMD, but the process various in different body sites [ 29 31 ]. Panagiotis Anagnostis et al considered that serum cholesterol directly affects bone dyslipidemia via inhibiting osteoblast differentiation, accumulating in the subendothelial area of bone arteries, and activating oxidative stress in bone marrow microcirculation [ 32 ]. Among our representative US participants, a higher total cholesterol was tied with a lower total BMD in participants aged 20–59 years.…”
Section: Discussionmentioning
confidence: 99%
“…Our results found that dyslipidemia was associated with an increased risk of osteoporosis. Dyslipidemia may cause increased oxidative stress and systemic inflammation, further leading to increased osteoclast activity and decreased bone formation [ 33 , 34 ]. Higher blood pressure was found to be associated with increased risk of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%